Fasting Versus Nonfasting and Low-Density Lipoprotein Cholesterol Accuracy. Issue 1 (2nd January 2018) - Sathiyakumar, Vasanth; Park, Jihwan; Golozar, Asieh; Lazo, Mariana; Quispe, Renato; Guallar, Eliseo; Blumenthal, Roger S.; Jones, Steven R.; Martin, Seth S.
Abstract : Background: Recent recommendations favoring nonfasting lipid assessment may affect low-density lipoprotein cholesterol (LDL-C) estimation. The novel method of LDL-C estimation (LDL-CN ) uses a flexible approach to derive patient-specific ratios of triglycerides to very low-density lipoprotein cholesterol. This adaptability may confer an accuracy advantage in nonfasting patients over the fixed approach of the classic Friedewald method (LDL-CF ). Methods: We used a US cross-sectional sample of 1 545  634 patients (959 153 fasting ≥10–12 hours; 586 481 nonfasting) from the second harvest of the Very Large Database of Lipids study to assess for the first time the impact of fasting status on novel LDL-C accuracy. Rapid ultracentrifugation was used to directly measure LDL-C content (LDL-CD ). Accuracy was defined as the percentage of LDL-CD falling within an estimated LDL-C (LDL-CN or LDL-CF ) category by clinical cut points. For low estimated LDL-C (<70 mg/dL), we evaluated accuracy by triglyceride levels. The magnitude of absolute and percent differences between LDL-CD and estimated LDL-C (LDL-CN or LDL-CF ) was stratified by LDL-C and triglyceride categories. Results: In both fasting and nonfasting samples, accuracy was higher with the novel method across all clinical LDL-C categories (range, 87%–94%) compared with the Friedewald estimation (range, 71%–93%; P ⩽0.001). With LDL-C <70 mg/dL, nonfasting LDL-CN accuracy (92%) was superior to LDL-CF accuracy (71%; P <0.001). In this LDL-C range, 19% of fasting and 30% of nonfasting patients had differences ≥10 mg/dL between LDL-CF and LDL-CD, whereas only 2% and 3% of patients, respectively, had similar differences with novel estimation. Accuracy of LDL-C <70 mg/dL further decreased as triglycerides increased, particularly for Friedewald estimation (range, 37%–96%) versus the novel method (range, 82%–94%). With triglycerides of 200 to 399 mg/dL in nonfasting patients, LDL-CN <70 mg/dL accuracy (82%) was superior to LDL-CF (37%; P <0.001). In this triglyceride range, 73% of fasting and 81% of nonfasting patients had ≥10 mg/dL differences between LDL-CF and LDL-CD compared with 25% and 20% of patients, respectively, with LDL-CN . Conclusions: Novel adaptable LDL-C estimation performs better in nonfasting samples than the fixed Friedewald estimation, with a particular accuracy advantage in settings of low LDL-C and high triglycerides. In addition to stimulating further study, these results may have immediate relevance for guideline committees, laboratory leadership, clinicians, and patients. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01698489. Abstract : Supplemental Digital Content is available in the text.